ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (ADD) DAN PENDAPATAN DESA KECAMATAN BELAWA KABUPATEN WAJO (STUDI KASUS PADA DESA LEPPANGENG) - Desi Darma Yanti; Sariana Damis (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2022)
The village has a function as the closest government center for the community. This study aims to analyze the accountability of village fund allocation (ADD) and analyze the accountability of Leppangeng Village Income, Belawa District, Wajo Regency. Data collection techniques by conducting interviews, observations and documentation. There were 7 informants in this study who were involved in Village Fund Allocation (ADD) and Village Revenue accountability. The data analysis technique in this study is qualitative with a descriptive analysis approach that describes the accountability of Village Fund Allocation (ADD) and Village Income based on the planning, implementation and accountability system in the Regulation of the Minister of Home Affairs Number 20 of 2018 concerning Village Financial Management. The results showed that the Management of Village Fund Allocation (ADD) and Village Revenue both administratively and technically by applying the principles of accountability supported by the principles of transparency, accountability, and participation. The management is also in accordance with applicable regulations, although there are still some obstacles faced by the Village Apparatus.